2021 DORIS definition of remission in SLE: final recommendations from an international task force. Issue 1 (24th November 2021) - van Vollenhoven, Ronald F; Bertsias, George; Doria, Andrea; Isenberg, David; Morand, Eric; Petri, Michelle A; Pons-Estel, Bernardo A; Rahman, Anisur; Ugarte-Gil, Manuel Francisco; Voskuyl, Alexandre; Arnaud, Laurent; Bruce, Ian N; et al.
Abstract : Objective: To achieve consensus on a definition of remission in SLE (DORIS). Background: Remission is the stated goal for both patient and caregiver, but consensus on a definition of remission has been lacking. Previously, an international task force consisting of patient representatives and medical specialists published a framework for such a definition, without reaching a final recommendation. Methods: Several systematic literature reviews were performed and specific research questions examined in suitably chosen data sets. The findings were discussed, reformulated as recommendations and voted on. Results: Based on data from the literature and several SLE-specific data sets, a set of recommendations was endorsed. Ultimately, the DORIS Task Force recommended a single definition of remission in SLE, based on clinical systemic lupus erythematosus disease activitiy index (SLEDAI)=0, Evaluator's Global Assessment <0.5 (0–3), prednisolone 5 mg/day or less, and stable antimalarials, immunosuppressives, and biologics. Conclusion: The 2021 DORIS definition of remission in SLE is recommended for use in clinical care, education, and research including clinical trials and observational studies.